Morphological and Microanatomical Transitions at the Proventriculus-Gizzard Junction in Post-hatch Guinea Fowls (Numida meleagris) - Senthamil Selvan, P. (Indian Journal of Veterinary Anatomy, 2020)
The stomach of guinea fowl had a glandular proventriculus and a muscular gizzard like domestic fowl. The caudal end of the proventriculus lead to the gizzard and opened in its cranial blind sac. The junction between these two compartments was short and had a relatively narrow circumference. The luminal surface of this zone lacked both the macroscopic papilla of proventriculus and the protective yellowish koilin of gizzard. Histological tunics were same that of the proventriculus and gizzard but revealed transitions: the plicae lead to arches, sulci transformed to tubular glands, muscularis mucosae extended as inner longitudinal muscle layer of blind sacs, loss of submucosal glands, well developed circular muscle layer and thinner outer longitudinal muscle layer that was lost in the regions of gizzard. The outermost layer was the serosa.